The Effect of Intellectual Intelligence (IQ) and Emotional Intelligence (EQ) on Student Mathematics Learning Outcomes - Rizky Mulyani; Riri Syafitri Lubis (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
It will be possible to determine whether the learning objectives have been achieved by assessing the learning outcomes. In addition to intellectual intelligence, emotional intelligence is another factor that determines students' learning outcomes. This study aimed to determine how intellectual intelligence (IQ) and emotional intelligence (EQ) influence the mathematics learning outcomes of grade XI students of MAS TPI Sawit Seberang. Based on the hypothesis proposed, intellectual intelligence (IQ) and emotional intelligence (EQ) influence the mathematics learning outcomes of grade XI students of MAS TPI Sawit Seberang. The type of research used is quantitative research with an ex post facto method. The research instruments were an intellectual intelligence (IQ) questionnaire of 15 statements, an emotional intelligence (EQ) questionnaire of 22 valid statements, and odd semester student math report cards as data on student math learning outcomes. The data analysis techniques used were descriptive statistical analysis, prerequisite tests, and hypothesis testing. The research findings are that 62.5% of students have high-category intellectual intelligence, 72.73% have moderate-category emotional intelligence, and 98.86% have very high-category math learning outcomes. From the results of the research that has been done, the researchers draw several conclusions: (1) Intellectual intelligence (IQ) influences the mathematics learning outcomes of XI grade students of MAS TPI Sawit Seberang. (2) emotional intelligence (EQ) influences the mathematics learning outcomes of XI grade students of MAS TPI Sawit Seberang. (3) There is an effect of intellectual intelligence (IQ) and emotional intelligence (EQ) simultaneously on the mathematics learning outcomes of XI grade students of MAS TPI Sawit Seberang. Furthermore, it is expected to conduct research with other variables to determine the effect of other variables on math learning outcomes. In addition, a more sustainable testing method, such as testing conducted periodically during the student's learning year, should be used. This method will help more comprehensively and accurately determine the relationship between IQ, EQ, and student math learning outcomes.